Unification of Logistic Demands of Small-scale Enterprises as Solution of Urban Traffic Congestion Problem - Petar, Saša; Ivaković-Babić, Morana (Promet - Traffic&Transportation, 2012)
The development of information and telecommunication technologies, apart from accelerating the information flows, increasing efficiency on the market and other business changes, results also in the reduction of the number of employees in companies. With the application of new information and telecommunication technologies even companies with a single employee in certain activities (publishing, counselling, tourism, etc.) can successfully compete with larger companies, which leads to an increased number of logistic service demands. A large number of small enterprises create a large number of small orders which have to be delivered in the same unit of time, thus causing increased congestion of roads, especially in urban areas. Although information transport, due to the mentioned technologies, has become to a large extent virtual, the transport of people and cargo continues to operate in a three-dimensional space (recognizing the time dimension as an important factor for calculating the business efficiency). The application of the model from the paper makes it possible to confirm the thesis of increased traffic congestion as consequence of the technological development and to emphasise the need to find a solution in the form of logistic and distribution centres for small and mid-size enterprises. The companies that offer logistic and distribution services may become centres for small and mid-size enterprises, thus offering a solution that maintains the speed and efficiency and avoids costs of congestions and delays.